Reclamation and Establishment: The Missionary Route and Belief Practice of The Christian and Missionary Alliance in the Late Qing Dynasty in the Diocese of Central China (1892-1899) - NI, Buxiao (Journal of Research for Christianity in China (JRCC), 2025)
The Christian and Missionary Alliance is the product of the American missionary movement in the late nineteenth century. Since the establishment of the missionary organization, it has sent missionaries to open up gospel workshops in China. The Christian and Missionary Alliance has established missionary strategies in China and divided different mission areas in China. Among them, the Central China mission area is the main line described in this article. It plans to build mission stations of different sizes, carry on parade sermons, build personal friendships, and run schools to spread the Christian faith. Its general work has something in common with the affairs of many missionary organizations in China. They not only have the spirit of the universal Christian missionary movement, but also have practical experience in the local church. Missionaries built a stable and long-term relationship network with the local believers in fixed places such as villages, homes, churches, etc., from understanding, accepting to converting to Christianity. Although they had to pay a certain amount of interpersonal and social costs due to conversion, they relied on the church’s religious relationship and religious experience to gain internal cohesion among Christians. Furthermore, as the Christian and Missionary Alliance in Central China paid more attention to traveling preaching, missionaries held the religious belief of saving souls before Christ’s second coming, and opened up missionary stations in Hunan that were difficult to break through in the past, thus realizing the role of pioneering pioneers, which is the first Christian Mission Association stationed in Hunan Province. This development model not only meets the missionaries’ expectations of "unreached land", but also marks that the Christian and Missionary Alliance has a direct evangelistic route in Central China.